Commentary: Small Pacific states and media freedom: A Kiribati case study - Taberannang Korauaba (Asia Pacific Network, 2007)
For more than 50 years, the governments of Kiribati have manipulated the affairs of the Broadcasting and Publications Authority (BPA). The authority runs a radio station and newspaper reaching the majority of the population of Kiribati. The interference is simply a warning to those  working for the authority that they do not have freedom to inform the public. In practice, the political opposition would oppose this interference, describing it as draconian and demanding more media freedom. But when the  opposition came to power, it would also restrict the work of  journalists. Thus reporters have often been caught in the crossfire between the politicians and are fearful of their future. Some journalists have been accused of being anti-government or sanctioning stories that embarrass the political leaders. This commentary explains—from the firsthand experience of this journalist—why in the digital era small Pacific nations such as Kiribati face a more fundamental issue: protecting the public’s right to know.